Analisis Faktor Penyebab Stock Out Dan Stagnant Pada Pelayanan Farmasi Rumah Sakit Di Indonesia Serta Upaya Pencegahannya - Rasendah, Rasendah; Andriani , Helen (Jurnal sosial dan sains, 2025)
Pharmaceutical quality management is an important process in ensuring that pharmaceutical services meet predetermined standards and provide optimal benefits for patients. However, stockout and stagnant problems are still often found that interfere with the smooth service to patients. This study aims to identify the factors that cause stock out and stagnation and formulate a prevention strategy. The method used is a literature review of six national articles published from 2021 to 2025, with a focus on hospital pharmaceutical institutions in Indonesia. The results of the study show that the main causes include inaccurate planning of drug needs, delays in distribution from suppliers, inconsistencies in the number and competence of pharmaceutical personnel, and the lack of optimal pharmaceutical management information systems. To overcome these problems, recommended strategies include consumption data-based planning, the use of integrated information systems, periodic stock audits, training of pharmaceutical personnel, and increased coordination with distributors. It is hoped that this finding can be the basis for improving the pharmacy logistics system of hospitals in Indonesia to ensure the availability of effective and efficient drugs